Study on Transformation Mechanism and Kinetics of α’ Martensite in TC4 Alloy Isothermal Aging Process - Hui Yu; Wei Li; Songsong Li; Haibei Zou; Tongguang Zhai; Ligang Liu (Crystals, 2020)
The law of microstructure evolution and transformation mechanism of the α′ martensite decomposition during 400−600 °C were studied by the isothermal dilatometry. The transformation process of α′ martensite was quantitatively characterized based on Johnson−Mehl−Avrami (JMA) model, and the microstructure evolution under different aging processes was observed and compared on Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). The results showed that α′ → α + β is the elemental diffusion transformation, the position and shape of the precipitate gradually change with the holding time and temperature. The decomposition rate of α′ martensite was positively correlated with the aging temperature. The whole transformation process was divided into two stages based on the value of the Avrami exponent n, and the corresponding average values of the transformation activation energies Q are 46.1 kJ/mol and 116.8 kJ/mol, respectively. The calculated model had good agreement with the experimental data, and the transformation curve of α′ martensite with time and temperature during the isothermal aging at 400−600 °C was drawn.